Pemurnian Asap Cair Hasil Torefaksi Cangkang Sawit dengan Cara Destilasi dan Filtrasi dengan Arang Aktif: Purification of Liquid Smoke from Torrefaction of Palm Oil by Distillation and Filtration with Activated Charcoal - Karelius, Karelius; Rosmainar, Lilis; Novia Toemon, Angeline; Dirgantara, Made (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Palangka Raya, 2020)
The liquid smoke produced from the torrefaction process of oil palm shells has the potential to be used as an antiseptic base for hand sanitizer and disinfectant products. It is due to its high phenol and acetic acid content. Apart from phenol and acetic acid, there are many other compounds that must be separated in the hope of obtaining liquid smoke with the main components of acetic acid and phenol, which function as antibacterial agents. This research begins with the production of liquid smoke through a torrefaction process. The liquid smoke obtained is distilled at 150 oC and followed by adsorption with activated charcoal for the purification process. The pH value and acetic acid content in the purified liquid smoke were determined and analyzed using GC-MS to determine the chemical compounds. The pH value has decreased after the refining process by distillation, and activated charcoal is inversely proportional to the increase in acetic acid levels after purification. Based on GC-MS analysis results, it can be seen that the levels of acetic acid, phenol, propanoic acid, and 2-propanone increased after distillation. The loss of 1,2-Benzenediol and 2-Furancarboxaldechde compounds shows that distillation of liquid smoke at 150oC is effective for separating the heavy fraction of liquid smoke. Furthermore, the distilled liquid smoke is filtered using activated charcoal. The GC-MS analysis results showed that the filtration results with activated charcoal could increase acetic acid and propanoic acid levels in liquid smoke.